Janus Kinase Inhibitors, Monoclonal Antibodies, and Fecal Microbiota Transplantation: Promising Therapies for Ulcerative Colitis - Rozak, Miftahul; Katz, Michael D; Lolita, Lolita (Clinical and Pharmaceutical Sciences Journal, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease involving genetic, environmental, immunological, and microbial factors. Traditional treatments often fail in certain patient populations, necessitating exploration of more personalized therapies. This review aims to evaluate the efficacy, safety, and clinical potential of three emerging therapies for UC: Janus kinase (JAK) inhibitors, anti-TL1A monoclonal antibodies, and fecal microbiota transplantation (FMT). This narrative review was conducted by searching PubMed and Google Scholar for relevant peer-reviewed literature. Inclusion criteria focused on studies published in the last 10 years that investigated the mechanisms, clinical efficacy, or safety of JAK inhibitors, anti-TL1A antibodies, or FMT in UC. Both randomized controlled trials and observational studies were included. This narrative review explores emerging therapeutic strategies for ulcerative colitis, including Janus kinase inhibitors, monoclonal antibodies, and fecal microbiota transplantation. These approaches may support personalized treatment planning, particularly in patients who are refractory to conventional therapies.JAK inhibitors including tofacitinib, upadacitinib, and filgotinib demonstrated effectiveness in inducing and maintaining remission, although safety profiles varied based on selectivity. Anti-TL1A monoclonal antibodies, particularly PF-06480605 and tulisokibart, showed dual anti-inflammatory and anti-fibrotic activity, especially in patients with specific genetic biomarkers. FMT emerged as a non-pharmacological intervention capable of modulating gut microbiota and mucosal immunity, contributing to clinical and endoscopic remission in patients refractory to standard treatments. These three therapeutic modalities represent a significant shift toward individualized, pathophysiology-based treatment of UC. Future research should focus on biomarker-guided therapy selection, optimization of FMT protocols, and long-term safety data to support integration into clinical practice. Keywords: Fecal microbiota transplantation, janus kinase inhibitors, monoclonal antibodies, ulcerative colitis